Coiled-coil domain-containing protein 69 (CCDC69) acts as a scaffold and a microtubule-destabilizing factor to regulate central spindle assembly - Pal, Debjani (Kansas State University, 2010)
Proper regulation of mitosis and cytokinesis is fundamentally important for all living organisms. During anaphase, antiparallel microtubules are bundled between the separating chromosomes, forming the central spindle (also called the spindle midzone), and the myosin contractile ring is assembled at the equatorial cortex. Regulators of central spindle formation and myosin contractile ring assembly are mostly restricted to the interdigitated microtubules of central spindles and they can be collectively called midzone components. It is thought that characteristic microtubule configurations during mitosis and cytokinesis are dictated by the coordinated action of microtubule-stabilizing and -destabilizing factors. Although extensive investigations have focused on understanding the roles of microtubule-bundling/stabilizing factors in controlling central spindle formation, efforts have been lacking in aiming to understand how microtubule-destabilizing factors regulate the assembly of central spindles. This dissertation describes the role of a novel microtubule-destabilizing factor termed CCDC69 (coiled-coil domain-containing protein 69) in controlling the assembly of central spindles and the recruitment of midzone components. Endogenous CCDC69 was localized to the nucleus during interphase and to the central spindle during anaphase. Exogenous expression of CCDC69 in HeLa cells destabilized microtubules and disrupted the formation of bipolar mitotic spindles. RNA interference (RNAi)-mediated knockdown of CCDC69 led to the formation of aberrant central spindles and interfered with the localization of midzone components such as aurora B kinase, protein regulator of cytokinesis 1 (PRC1), MgcRacGAP/HsCYK-4, and pololike kinase 1 (Plk1) at the central spindle. CCDC69 knockdown also decreased equatorial RhoA staining, indicating that CCDC69 deficiency can impair equatorial RhoA activation and ultimately lead to cytokinesis defects. Four coiled-coil domains were found in CCDC69 and the C terminal coiled-coil domain was required for interaction with aurora B. Disruption of aurora B function in HeLa cells by treatment with a small chemical inhibitor led to the mislocalization of CCDC69 at the central spindle. Further, vitro kinase assay showed that Plk1 could phosphorylate CCDC69. Taken together, we propose that CCDC69 acts as a scaffold and a microtubule-destabilizing factor to control the recruitment of midzone components and the assembly of central spindles.
Keywords: Coiled-coil domain containing protein 69 (CCDC69); Microtubule-destabilizing factor; Central spindle assembly; Cell Cycle; Biology, Cell (0379); Biology, Molecular (0307); Chemistry, Biochemistry (0487)